2019
DOI: 10.3390/biomedicines7010004
|View full text |Cite
|
Sign up to set email alerts
|

α-Ketoglutaric Acid-Modified Carbonate Apatite Enhances Cellular Uptake and Cytotoxicity of a Raf-Kinase Inhibitor in Breast Cancer Cells through Inhibition of MAPK and PI-3 Kinase Pathways

Abstract: AZ628 is a hydrophobic Raf-kinase inhibitor (rapidly accelerated fibrosarcoma) currently in clinical trial of various cancer. The physicochemical properties of hydrophobic drugs that affect the drug-particle interactions and cause aggregation of drugs and particles might be the key aspect to impede effective drug delivery. Retaining smaller particle size is the prerequisite to overcome the opsonization and improve cytotoxicity in the targeted region. Carbonate apatite (CA), an attractive biodegradable vector, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The release of drug from the nanoparticle-based formulation depends on many factors including pH, temperature, drug solubility, desorption of the surface-bound or adsorbed drug, drug diffusion through the nanoparticle matrix, nanoparticle matrix swelling and erosion, and the combination of erosion and diffusion processes [57][58][59]. The influence of the pH-sensitive dissolution of CA, CMCA, and α-KAMCA NPs ensured drug release in a acidic microenvironment [28,40] in our former study. An in vitro turbidity test ( Figure 11) was conducted by modeling physiological pH (7.4) and endosomal acidic pH (6.5-5.0), and the NPs were subjected to these environments to ensure pH sensitivity.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The release of drug from the nanoparticle-based formulation depends on many factors including pH, temperature, drug solubility, desorption of the surface-bound or adsorbed drug, drug diffusion through the nanoparticle matrix, nanoparticle matrix swelling and erosion, and the combination of erosion and diffusion processes [57][58][59]. The influence of the pH-sensitive dissolution of CA, CMCA, and α-KAMCA NPs ensured drug release in a acidic microenvironment [28,40] in our former study. An in vitro turbidity test ( Figure 11) was conducted by modeling physiological pH (7.4) and endosomal acidic pH (6.5-5.0), and the NPs were subjected to these environments to ensure pH sensitivity.…”
Section: Discussionmentioning
confidence: 55%
“…CMCA, SMCA (succinate-modified carbonate apatite), and α-KAMCA NPs were prepared by modifying CA with citrate, containing three carboxyl groups, succinate, containing two carboxyl groups, and ketoglutarate, containing one ketone group and two carboxylic groups, respectively. In our previous experiment [28,39,40], we showed that the presence of carboxylic and ketone groups in the chemical structure has an influential role in determining the particle size and the binding affinity of the drugs toward the NPs. The α-KAMCA NPs exhibited the desired particle size with a large number of resultant particles and a folded larger surface morphology with rapid dissolution at acidic pH in the microenvironment, resulting in more significant cytotoxicity than the CA NPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were seeded in 24-well plates with a density of the 50,000 cells per well and were incubated for 24 h [ 41 ]. After 24 h incubation, the media was removed and was replaced with the free PTX and PTX-NaCNs with final concentrations of 5 and 10 µM.…”
Section: Methodsmentioning
confidence: 99%